2021
DOI: 10.1017/jmo.2021.60
|View full text |Cite
|
Sign up to set email alerts
|

Impact of institutional support on educators' subjective well-being during the transition to virtual work due to COVID-19 lockdown

Abstract: The coronavirus disease-2019 pandemic changed regular life and work around the world. Educational institutions moved to a virtual environment, in many cases without any experience and preparation. This paper explores the impact of institutional support on educators' subjective well-being during the pandemic lockdown. A quantitative study was conducted in Lithuania with 1,851 educators in April 2020. Institutional support was found to have a positive impact on work–life balance and well-being, as well as reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…When we use well-being in reference to teachers, we are referring to their work at their educational institutions. Teachers’ well-being is influenced by a myriad of contextual factors, such as institutional resources and support ( Kumpikaitė-Valiūnienė et al, 2021 ), workload, or students’ behavior in the classroom ( Chan et al, 2021 ), as well as by teacher-specific personal variables such as personality or engagement at work ( Jelińska and Paradowski, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…When we use well-being in reference to teachers, we are referring to their work at their educational institutions. Teachers’ well-being is influenced by a myriad of contextual factors, such as institutional resources and support ( Kumpikaitė-Valiūnienė et al, 2021 ), workload, or students’ behavior in the classroom ( Chan et al, 2021 ), as well as by teacher-specific personal variables such as personality or engagement at work ( Jelińska and Paradowski, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… 21 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 A study in Lithuania found positive correlations between institutional support on educators’ subjective well-being and work-life balance, and that greater institutional support reduced burnout. 57 Despite educators in the current study not feeling supported constantly, the radiography students felt supported by their lecturers. 31 …”
Section: Resultsmentioning
confidence: 60%
“…Several implications could be made based on the findings and discussions above. Firstly, it is obvious that during the unexpected transition to virtual teaching, teachers needed help with not only technological and informational resources but also advice on the implementation of their teaching tasks (Kumpikaitė-Valiūnienė et al, 2021). In this context, learner autonomy and learning assessment are among the most challenging tasks in second language teaching due to time and technical constraints.…”
Section: Discussionmentioning
confidence: 99%